JARGON KOMUNITAS PENCINTA ALAM: STUDI KASUS KOMUNITAS PENCINTA ALAM SWAPALA KALIJAGA SMA N 1 DEMAK - Ika Shofia Rani; Eva Ardiana Indrariani; Siti Ulfiyani (Teks: Jurnal Penelitian Bahasa, Sastra, dan Pengajarannya, 2022)
ABSTRACTThis study aims to describe form function the use of jargon in the student’s mountaineering community of Swapala Kalijaga SMA N 1 Demak. The use of jargon in a community in addition to interacting has the aim of creating a language that is only understand by the community that is formed. The research used a qualitative research approach with a sociolinguistic theoretical approach. The data was collected using a method watch free to talk, conservation, recording, notes, and interviews to find the function of using jargon. The text were analyzed using carried out by outlining the forms of jargon that have their respective use functions found in the community of Swapala Kalijaga SMA N 1 Demak. From the research, it concluded that jargon is used to interact among fellow members as well of a community. The results show that jargon from community of Swapala Kalijaga SMA N 1 Demak was 37 jargons. Jargon community of Swapala Kalijaga SMA N 1 Demak is divided into four forms (1)words forms, (2)phrase forms, (3)abbreviated forms, and (4)acronym forms. Each jargon used has its own function of use (1)information, (2)invitations, (3)identity, (4)rule, (5)enthusiasm, and (6)facilitate communication. Keywords: jargon, community, student’s mountaineering